Tensile Properties of Single Cellulosic Bamboo Fiber (Gigantochloa Scortechinii) Using Response Surface Methodology - Salih, Abeer Adel; Zulkifli, Rozli; Azhari, Che Husna (Taylor & Francis Inc, 2024)
Indexed by WOS/SCOPUS/ERA